Integral matrices as diagonal quadratic forms II - Koo, Bonsoo; Lee, Jungin (Linear and Multilinear Algebra, 2025)
For an integer (Formula presented.), let (Formula presented.) be the smallest positive integer m such that for every pairwise coprime integers (Formula presented.), every (Formula presented.) integral matrix can be represented by the diagonal quadratic form (Formula presented.). In this paper, we prove that (Formula presented.) and (Formula presented.) for every integer (Formula presented.).
Keywords: Diagonal quadratic forms; integral matrices; universal quadratic forms